2020
DOI: 10.1016/j.jmatprotec.2019.116549
|View full text |Cite
|
Sign up to set email alerts
|

A study on central crack formation in cross wedge rolling

Abstract: Cross wedge rolling (CWR) is an innovative roll forming process, used widely in the transportation industry. It has high production efficiency, consistent quality and efficient material usage. However, the continual occurrence of crack formation in the centre of the workpiece is a critical problem excluding the CWR technique from more safety-critical applications, in particular, aerospace components. The mechanisms of central fracture formation are still unclear because of a combination of complicated stress a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 27 publications
2
25
0
Order By: Relevance
“…It was found that the criteria which take into account, at least indirectly, the effect of shear stresses yield better results. Similar observations were made by Zhou et al [ 20 ]. In-depth analyses of the stress state in the rotary compression tests and CWR [ 21 ] revealed that the stresses are not identical, which may affect the accuracy of modelling material fracture in CWR.…”
Section: Introductionsupporting
confidence: 91%
“…It was found that the criteria which take into account, at least indirectly, the effect of shear stresses yield better results. Similar observations were made by Zhou et al [ 20 ]. In-depth analyses of the stress state in the rotary compression tests and CWR [ 21 ] revealed that the stresses are not identical, which may affect the accuracy of modelling material fracture in CWR.…”
Section: Introductionsupporting
confidence: 91%
“…Furthermore, in industry, the loading condition on the workpiece is much more complex, as studied in the previous work [5], being subjected to triaxial stress state, cyclic loading, and large plastic strain. This complex loading condition accelerates the decohesion between the inclusion and steel matrix.…”
Section: Fracture Mechanisms In Cwrmentioning
confidence: 99%
“…Yang et al [4] studied central crack formation on a microstructural scale and revealed the ductile fracture mechanism of steels at high temperature. Zhou et al [5] considered the combined effects of the shear and normal stress and proposed a novel fracture criterion, which was validated quantitively. However, there is not an agreement on the fracture mechanisms of central crack formation due to the complex mechanical and microstructural behaviours during CWR.…”
Section: Introductionmentioning
confidence: 99%
“…In this equation, A and B are material constants, presenting the contribution ratios of the maximum shear stress τ m and the rst principal stress σ 1 to central crack formation. Zhou et al [17,22] has validated this criterion by low ductility materials, including 27 groups of pure aluminium (highly strained) CWR tests and 16 groups of CWR tests with plasticine/ our composites. When the material is at high ductility, an energy-based fracture criterion will be employed considering the severe plastic deformation occurs before nal fracture, as presented in Eq.…”
Section: Proposal Of a New Central Crack Criterionmentioning
confidence: 99%
“…Recently, Pater et al [16] proposed a damage model considering the fracture mechanisms, void formation and shear fracture, achieving high accuracy in C45 steel at the elevated temperature. Zhou et al [22] proposed a physics-based fracture criterion capable of predicting the central cracks in 27 groups of CWR tests on pure aluminium AA1100 with different die geometries. However, these models have never been validated by different materials, which exhibit different fracture mechanisms.…”
Section: Introductionmentioning
confidence: 99%